1995
DOI: 10.2175/106143095x131420
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface flow wetlands—A performance evaluation

Abstract: This paper evaluates data collected by the authors as well as other individuals and agencies at operational subsurface flow constructed wetlands. The purpose of the evaluation was to identify the influence of hydraulic loading, organic loading, hydraulic residence time (HRT) on removal performance for biochemical oxygen demand (BOD), total suspended solids (TSS), nitrogen and phosphorus. The results indicate that BOD and TSS removal can be very effective at a relatively short HRT and that BOD removal exhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 3 publications
3
50
0
3
Order By: Relevance
“…Similarly, a linear proportional relationship was also found between effluent NH 4 + -N concentration and NH 4 + -N mass loading rate (R 2 = 0.5628). Basically, the linear relationships between BOD and NH 4 + -N removal and their loading rates were coincident to the conclusion reported by other researchers (Reed and Brown, 1995;Varrier and Dahab, 2001). By the way, no significant differences (p > 0.05) were seen on the removal rates of BOD 5 and NH 4 + -N with the HRT less than 2.5 h., between 2.5 h. and 2.8 h. and higher than 2.8 h. However, significant differences (p < 0.05) were concluded on the TSS removal rates with HRT less than 2.5 h., between 2.5 h. and 2.8 h. and higher than 2.8 h. Effluent BOD or NH 4 + -N concentration had a significant correlation (p = 0.003) with its mass loading rate in the treatment system.…”
Section: Treatment Efficiencysupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, a linear proportional relationship was also found between effluent NH 4 + -N concentration and NH 4 + -N mass loading rate (R 2 = 0.5628). Basically, the linear relationships between BOD and NH 4 + -N removal and their loading rates were coincident to the conclusion reported by other researchers (Reed and Brown, 1995;Varrier and Dahab, 2001). By the way, no significant differences (p > 0.05) were seen on the removal rates of BOD 5 and NH 4 + -N with the HRT less than 2.5 h., between 2.5 h. and 2.8 h. and higher than 2.8 h. However, significant differences (p < 0.05) were concluded on the TSS removal rates with HRT less than 2.5 h., between 2.5 h. and 2.8 h. and higher than 2.8 h. Effluent BOD or NH 4 + -N concentration had a significant correlation (p = 0.003) with its mass loading rate in the treatment system.…”
Section: Treatment Efficiencysupporting
confidence: 90%
“…Kemp and George (1997) also reported that the effluent NH 4 + -N concentration could have obvious reduction when the HRT of subsurface flow constructed wetland was increased from 1.7 days to 3.9 days. However, Reed and Brown (1995) claimed that BOD removal could be very effective at a relatively short HRT and effective nitrogen removal might require a longer HRT. Although this treatment system showed certain degree of treatment efficiency on pollutants at lower HRTs, further studies might be required to confirm whether higher HRT will improve the treatment efficiency of gravel contact oxidation system.…”
Section: Treatment Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to providing enhanced evapotranspiration rates in 2014 and 2015, vegetation helped establish a source of organic carbon for denitrifying bacteria to utilize for reduction processes [26]. Vegetation establishment could have, in theory, been improved by water level drawdown in the wetland to promote growth in year 1.…”
Section: Vegetationmentioning
confidence: 99%
“…In developing countries, such treatment plants are not considered as an economically viable option. Treatment should not also let the nutrient-enriched wastewater down the drains and nutrients and water should be reused in productive use by closing the nutrient loop [1]. Treatment wetland systems exemplify systems of low-cost, low-tech, low maintenance and minimal energy demanding system and therefore, can be promoted as appropriate eco-based solutions to wastewater problem.…”
Section: Introductionmentioning
confidence: 99%